Another Fukushima effect? Risk perceptions of nuclear power and Fukushima treated radioactive water on the acceptance of nuclear power in South Korea - Kim, Kyunghwan; Kim, Seoyong (Journal of Risk Research, 2025)
The 2011 nuclear disaster in Fukushima, Japan, impacted the world’s acceptance of nuclear power. In addition, the discharge of Fukushima treated water in 2023 poses a new risk, especially for Koreans living in close proximity to Japan. The research questions of this study are whether the risk perception of the Fukushima nuclear accident in Japan still affects the acceptance of nuclear power among Koreans, and whether it intervenes in the effect of the recent risk perception of Fukushima treated radioactive water on the acceptance of nuclear power. A survey study of 1898 South Koreans conducted May 17–23, 2024 using web methods with quota sampling for representativeness. According to the results of the survey, the variables with the highest explanatory power in explaining the acceptance of nuclear power in Korea are: trust > trust in the supervisory organization for FTRW > knowledge > risk perception of FTRW (Fukushima Treated Radioactive Water) > risk perception of Fukushima nuclear accident > risk perception of nuclear power generation. It is worth noting that trust plays an important role in these results, with each of the three risk perception variables playing a critical role. In addition, impact of risk perception of the Fukushima nuclear accident and Fukushima treated water on the acceptance of nuclear power generation among Koreans suggests that risk judgment has cross-border effects. In addition, the perceived risk of Fukushima nuclear accident moderates the effectof knowledge and trust on the acceptance of nuclear power plants. This study contributes to the literature by revealing the long-term effects of the Fukushima accident and cross-border risk perception mechanisms, providing important implications for nuclear policy development through effective risk communication and trust-building strategies.
Keywords: Acceptance of nuclear power; Cross-border; Fukushima; Fukushima nuclear accidents; Fukushimum treated water; Nuclear power generation; Power; Radioactive water; Risk communication; South Korea; acceptance of nuclear power; Fukushima nuclear accident; Fukushima treated water; nuclear waste; Risk communication